Determinant Cost of Capital - Nur Khosim; Adler Haymans Manurung (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this paper is to look at the determinants of a company's cost of capital. This study conducted a literature review with the aim of identifying the factors that affect the cost of capital of a company. The research shows that profitability, liquidity, tax, growth and firm size are the determinants that affect the cost of capital of a firm. Further research shows a positive correlation between the cost of capital and profitability, liquidity, growth and firm size. The capital arrangement of a firm is determined based on the pecking order theory and trade-off theory while still considering the cost elements associated with it.